Pengaruh Biaya Produksi dan Volume Penjualan terhadap Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Sektor Food and Beverage di BEI - Dwi Utami; Ambarwati Akib; Sri Utami (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the effect of production costs and sales volume on profit with firm size as a moderating variable in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study used a quantitative approach with an associative research design. The data used were secondary data obtained from annual financial statements of food and beverage companies listed on the IDX. The sampling technique used purposive sampling and obtained 110 observations. The analysis method employed was Moderated Regression Analysis (MRA) using IBM SPSS Statistics. The results of the study indicate that production costs do not have a significant effect on company profit. Meanwhile, sales volume has a positive and significant effect on profit. Firm size has a negative and significant effect on profit. Furthermore, firm size is unable to moderate the relationship between production costs and profit as well as the relationship between sales volume and profit. The coefficient of determination test shows that the independent and moderating variables are able to explain 56.8% of the variation in company profit, while the remaining 43.2% is explained by other variables outside the research model. This study implies that companies need to focus more on increasing sales volume and improving operational efficiency to enhance profitability.